2013
DOI: 10.3390/rs5104900
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Tree Cover in an Agricultural Parkland of Senegal Using Rule-Based Regression Tree Modeling

Abstract: Abstract:Field trees are an integral part of the farmed parkland landscape in West Africa and provide multiple benefits to the local environment and livelihoods. While field trees have received increasing interest in the context of strengthening resilience to climate variability and change, the actual extent of farmed parkland and spatial patterns of tree cover are largely unknown. We used the rule-based predictive modeling tool Cubist® to estimate field tree cover in the west-central agricultural region of Se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 31 publications
1
21
0
Order By: Relevance
“…The same is true for the Landsat based map developed by Sexton et al (2013) (not shown for brevity). This supports existing studies (Herrmann et al, 2013;Gessner et al, 2013) which detect a generally very low tree cover in global products over the Sahel. It further demonstrates that, although the spatial pattern in the MOD44B product is similar and the relation linear to ground data, MOD44B delivers only partial information on the total woody cover in semi-arid drylands, omitting small trees, shrubs and bushes.…”
Section: Differences Between Woody/tree Cover Mapssupporting
confidence: 79%
See 3 more Smart Citations
“…The same is true for the Landsat based map developed by Sexton et al (2013) (not shown for brevity). This supports existing studies (Herrmann et al, 2013;Gessner et al, 2013) which detect a generally very low tree cover in global products over the Sahel. It further demonstrates that, although the spatial pattern in the MOD44B product is similar and the relation linear to ground data, MOD44B delivers only partial information on the total woody cover in semi-arid drylands, omitting small trees, shrubs and bushes.…”
Section: Differences Between Woody/tree Cover Mapssupporting
confidence: 79%
“…Timesat has been widely used in the Sahel area to detect seasonal dynamics related to the phenology of vegetation and describing the shape of the annual vegetation curve reflected in satellite data (e.g. Horion et al, 2014;Herrmann et al, 2013;Fensholt et al, 2013). The derived seasonal metrics are summarized in Table 1 and illustrated in Fig.…”
Section: Extraction Of Satellite Seasonal Metricsmentioning
confidence: 99%
See 2 more Smart Citations
“…The technical framework of this study adapts local-scale approaches of modeling dryland woody cover 37,38 into reproducible regional/global scale assessments, as the unprece- of woody cover at selected sites served as an independent validation of the remote sensing mapping approach. To achieve a woody cover map of the entire area, the spatially detailed woody cover data derived from VHR images were used to train a gradient boost decision tree regressor to predict woody cover from PROBA-V NDVI and PALSAR-2 images at high resolution (100 m).…”
Section: Methodsmentioning
confidence: 99%